ESTRATÉGIAS UTILIZADAS POR UM APLICATIVO DE DELIVERY PARA CAPTAÇÃO DE CLIENTES EM E-COMMERCE (ADMPG Journal, 2023)
Restaurants are inserted in a competitive environment, always seeking to attract new customers to serve. With the advancement of technologies; emergence of e-commerce and due to the pandemic scenario, delivery applications have become an opportunity for restaurants to migrate to the internet and reach more people. The objective of this research is to know the strategies used by a delivery application, in order to understand how restaurants attract customers in the city of Manhuaçu (MG), to evaluate if the public perceives such actions of the application. A qualitative and quantitative research was carried out, with questionnaires and interviews with the main actors involved: responsible for the application, restaurants use the platform and final consumers. This study allowed us to know strategic actions of restaurants within the delivery application, the flow of information that users have access to, as well as the behavior and criteria of consumers. The final consumers presented a greater perception of value based on promotional discounts, the payment method, ease of use and the fact of making purchases without leaving home. Restaurants understand as main positive aspects the speed in using more e-commerce; the increase of transactions from the use of the application; possibility of serving a greater number of users. It is also considerable the dissatisfaction of final consumers with the delay of delivery of orders, a fact that should be reviewed by organizations.